A sensibilidade do diafragma em Diderot: um paradoxo do paradoxo - Clara Carnicero de Castro (O Que Nos Faz Pensar)
The reference to the diaphragm organ indicates a specific kind of sensibility. This meaning coexists with others in some of the most important writings of Diderot’s late work: Rêve de d'Alembert (1769), Éléments de physiologie (≈1782), Réfutation d'Helvétius (1783) and, above all, Paradoxe sur le comédiant (1773). This meaning is difficult to interpret because it unfolds in two: the diaphragm and the brain as two sensitive motors of the human body. The objective of this article is to present the problem of the diaphragm sensibility in Diderot, considering this twofold sense, to then contextualize the theory in the writings of naturalists and physicians of the time (Buffon, La Caze and Bordeu). Furthermore, we propose an interpretation consistent with this context.